Is the Fed reacting to stock price fluctuations? Evidence from the Internet bubble - Recordon, Eugenie (2006)
The second half of the 1990s saw a major bull market in equities in the United States, followed by a bear market that began in Spring 2000. This experience has led a number of academics, journalists, and businesspeople, to question the appropriate monetary policy response to sharp run-up in stock prices. The present study contributes to this line of research by assessing whether the Federal Reserve Bank (Fed) actually took into account stock prices when implementing its monetary policy during the Internet Bubble of the late 1990s. In 1993, Taylor (1993) claimed that a linear function of current inflation deviation from an inflation target and the output gap tracked the Fed funds rate fairly well between 1987 and 1992. Similarly, the empirical analysis carried out in this dissertation shows that this rule provides a good description of the monetary policy over the 1987-1995 period. However, the estimations over a more recent period seem to suggest that the Fed Funds rate did not follow the Taylor rule for the 1996-2006 period. Therefore, we wonder what can explain such a result. The hypothesis in this dissertation is that the weight of the two traditional variables from the Taylor rule has been reduced in favour of the increasing importance of a new variable to which the Fed has reacted over this period. The main result of this analysis actually indicates a decreased influence of inflation in monetary policy decisions over the period under consideration while the Fed was increasingly taking the fluctuations of stock prices into account. Even if stock prices fluctuations are not a stated goal of the US monetary policy, the reactions of the Fed to the extreme variations of stock prices during the Internet Bubble decreased the importance of the goals of price stability and sustainable growth, which was possible thanks to the reduced inflation observed over the period.